Study on the correlation between urinary retinol binding protein and nonalcoholic fatty liver disease - Li, Chuang; Kong, Weiwei; Kang, Lixia; Zhang, Weiqun; Wang, Weidong; Zhang, Tiehan (Journal of Medical Biochemistry, 2020)
Background: Nonalcoholic fatty liver disease (NAFLD) affects human health worldwide.Our objective was to explore the correlation between urinary retinol binding protein (URBP) and nonalcoholic fatty liver disease (NAFLD). Methods: This cross-sectional study included 445 NAFLD patients and 911 healthy controls. The URBP level and other parameters were measured. Results: The URBP level (expressed by the RBP/creatinine ratio) was higher in the NAFLD patients compared with the non-NAFLD patients. The urinary RBP/creatinine ratio was an independent risk factor for NAFLD after univariate and multivariate regression analysis, with the OR values of 2.271 (1.795–2.872, P < 0.001) and 2.338 (1.775–3.080, P < 0.001), respectively. The prevalence of the urinary RBP/creatinine ratio (groups 1, 2, 3, 4) was 20.0%, 17.3%, 27.3%, and 35.4%, respectively (P < 0.001), and the prevalence of NAFLD in the high urinary RBP/creatinine ratio group was significantly higher than that in the low urinary RBP/creatinine ratio group. Conclusions: Our results revealed that URBP was an independent risk factor for NAFLD.